Fiber optic gas sensor for air pollution detection - Ang, Soo Seng (2008)
This dissertation reports about the fabrication of the optical fiber chemical gas sensor to detect the presence and concentration of the two main air pollutants: Sulphur Dioxide (SO2) and Nitrogen Dioxide (NO2).